Efektivitas Senam Irama dalam Meningkatkan Perkembangan Motorik Kasar Anak Usia 5–6 Tahun - Zulfi Indah Nadya Fajrin; Anita Chandra D. S.; Ratna Wahyu Pusari; Fairuz Annisa (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study aims to examine the effect of rhythmic gymnastics on the gross motor development of children aged 5–6 years. The research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The sample consisted of 30 children divided into two groups, namely the experimental group and the control group, each comprising 15 children. Data were collected through observation using a gross motor development assessment instrument and analyzed using descriptive and inferential statistics. The results showed an improvement in gross motor skills in the experimental group after receiving rhythmic gymnastics treatment. The mean score increased from 23.8 (pretest) to 40.67 (posttest), while the control group increased from 22.2 to 32.33. Category distribution indicated that the experimental group was dominated by high and very high levels, whereas the control group remained in moderate and high categories. The findings indicate that rhythmic gymnastics has a positive effect on the gross motor development of children aged 5–6 years and can be used as an effective learning method in early childhood education.